Apostasia fujianica (Apostasioideae, Orchidaceae), a new Chinese species: evidence from morphological, genome size and molecular analyses - Li, Yuanyuan; Ma, Liang; Liu, Ding-Kun; Zhao, Xue-Wei; Zhang, Diyang; Ke, Shijie; Chen, Gui-Zhen; Zheng, Qinyao; Liu, Zhong-Jian; Lan, Siren (Phytotaxa, 2023)
After examining morphological, molecular and genome-size evidence, we here describe a new orchid species, Apostasia fujianica, from Fujian, China. Morphological comparisons indicated that A. fujianica is similar to A. shenzhenica and A. nipponica, whereas the former displayed distinct differences in habit, roots, leaves, inflorescences and fruit shape and size. Apostasia fujianica (341 Mb) has a smaller genome size than A. shenzhenica (471 Mb), A. ramifera (366 Mb) and A. fogangica (931 Mb). Molecular analyses from combined nuclear (ITS, Xdh, naD1) and plastid (matK, rbcL, psbA-trnH, trnL-trnF and trnS-trnG) datasets indicated that A. fujianica is sister to A. shenzhenica. These results support the status of A. fujianica as a new species, distinguished in many aspects from A. shenzhenica, A. ramifera and A. nipponica.